Universe of galaxies - Lima, Gastão B. (Cadernos de Astronomia, 2024)
Galaxies are fundamental structures in the Universe. The discovery of the extra-galactic nature of spiral nebulae only occurred in the mid-1920s. During the century that has passed since then, we have learned a lot about galaxies. This text describes how we came to the conclusion that the Universe is populated by galaxies, many similar to our own, the Milky Way. We will see how we classify galaxies, what their main properties are, how they form and evolve, and how they are distributed throughout the Universe.